Literature review: faktor-faktor yang berhubungan dengan health-seeking behavior dan quality of life pada pasien penderita asma - Sulistiawati, Sulistiawati; Hilmi , Indah Laily (Journal of Pharmaceutical and Sciences, 2024)
Background: Asthma affects approximately 335 million people worldwide and is the 14th most common disease globally in terms of disability, burden, and negative impact on individuals, society, and the economy. Asthma patients often experience a decline in condition due to sudden onset symptoms. Comorbid conditions such as depression and anxiety, changes in nighttime and early morning activities, and environmental factors such as cold air can affect the quality of life of asthma patients and influence their health-seeking behavior. Methods: This study used an observational design with a literature study approach. The databases used to obtain this article are PubMed and Scopus. Results: From the literature study results, 7 articles were analyzed that met the eligibility criteria according to the inclusion and exclusion criteria. The resulting factors are associated with health-seeking behavior and quality of life in asthma patients. Conclusion: This study states that factors associated with health-seeking behavior and quality of life in asthma patients include education, distance to health facilities, socio-economic factors, age, employment status, gender, obesity, and anxiety/depression.